2021
DOI: 10.3390/agronomy11071281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Animal Waste Based Digestate Fertilization on Soil Microbial Activities, Greenhouse Gas Emissions and Spring Wheat Productivity in Loam and Sandy Loam Soil

Abstract: The increasing quantities of organic residues are becoming one of the most important problems for climate change mitigation. Sustainable utilization technologies are required to minimize the effect of recycling on the environment. Nevertheless, treated residues should be part of the circular bioeconomy. One of the most promising processes is the biogas system, with the final products biogas and digestate, which contain valuable nutrients and are therefore suitable as agricultural fertilizers. However, there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The GHG fluxes from the soil mainly CO 2 , N 2 O and CH 4 were measured by the static chamber-gas chromatography technique. The chamber parameters, measurement of fluxes and gas chromatography were as described in previous studies (Doyeni et al, 2021a; Kanerva et al, 2007). The flux rate of each GHG was calculated based on the rate of change in GHG concentration within the chamber, estimated as the slope of the linear regression between the GHG concentration and gas sampling time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GHG fluxes from the soil mainly CO 2 , N 2 O and CH 4 were measured by the static chamber-gas chromatography technique. The chamber parameters, measurement of fluxes and gas chromatography were as described in previous studies (Doyeni et al, 2021a; Kanerva et al, 2007). The flux rate of each GHG was calculated based on the rate of change in GHG concentration within the chamber, estimated as the slope of the linear regression between the GHG concentration and gas sampling time.…”
Section: Methodsmentioning
confidence: 99%
“…The flux rate of each GHG was calculated based on the rate of change in GHG concentration within the chamber, estimated as the slope of the linear regression between the GHG concentration and gas sampling time. The CO 2 , N 2 O and CH 4 fluxes were determined from each pot by the closed-chamber equation indicated in a previous study (Doyeni et al, 2021a).…”
Section: Ghg Flux Measurementmentioning
confidence: 99%
“…A study in Korea showed that the application of liquid PM increased the biomass of green manure crops barley (Hordeum vulgare L.) and hairy vetch (Vicia villosa Roth) by more than 216 and 135%, respectively, compared with no application of PM during a 2-yr study period (Kang et al, 2020). Other studies (Šimon et al, 2016;Tampio et al, 2016) found that fertilization, especially in cow digestate manure under the application of field conditions increased yield, part of the reason was the yield of applying cow digestate manure was significantly higher than that of pig digestate manure (Doyeni et al, 2021), and in our study, the BR was pig digestate manure, the yield of BR treatment did not increase.…”
Section: Relationships Between Organic Materials and Grain Yieldmentioning
confidence: 99%
“…digestate (Doyeni et al, 2021). Furthermore, ST return also contributed to crop yields; it has been shown that ST return in combination with urea and controlled-release N fertilizer was beneficial in improving lint yield, N utilization, and soil N availability (C. Yang et al, 2022).…”
Section: Core Ideasmentioning
confidence: 99%
See 1 more Smart Citation